Comparative study of the biological properties of foetal and placental distal ends of human umbilical cord wharton's jelly mesenchymal stem cells - Yusoff, Zuraidah (2015)
Mesenchymal stem cells (MSC) are defined as a non-haematopoietic multipotent stem cells with the ability to self-renew; capable of differentiating into various mature cells and exert potent immunomodulatory activities on immune cells. These unique characteristics and properties of MSC had enabled them to be recognised as an attractive tool in stem cell based immunotherapy, gene therapy and regenerative medicine especially for fatal or incurable diseases. To date, many studies have demonstrated that MSC can be generated from various organs and tissues, such as birth-associated tissues including placenta, amnion and umbilical cord. Umbilical cord derived MSC (UC-MSC) has long been considered as an alternative to MSC that derived from bone marrow (BM-MSC) as they are regarded as medical waste with little ethical concern for research and easily culture expanded. The human umbilical cord (UC) comprises of various compartments such as two arteries, one vein, amnion, and Wharton’s jelly (WJ). Cells isolated from these compartments were found to be plastic adherent and able to differentiate into many cell types such as osteoblasts, adipocytes,chondrocytes, hepatocytes, neural and cardiac cells. Since MSC are migrating from foetal liver to the bone marrow at last trimester of pregnancy, thus the chances of MSC to be deposited at various compartments of umbilical cord will principally different too. Thus, the present study is aimed to determine a better anatomical part of umbilical cord which potentially yield a greater number and quality of MSC. In this present study, two distinguished anatomical parts of human umbilical cord Wharton’s jelly were consumed to generate MSC. These are foetal distal end (FE) that connected to the newborn baby and the placental distal end (PE) which is adjacent to the placenta. Mesenchymal stem cells were generated from the explants method where Wharton’s jelly of umbilical cord were minced up to paste-like state and cultured in the same condition. The generated WJ-MSC were characterised using a standard panel of surface markers and their ability to differentiate into osteoblasts and adipocytes followed by quantification of PCR gene expression. The immunomodulatory effect of MSC that generated from both ends were tested with mitogen activated T cells along with Jurkat cells through tritiated thymidine assay, cell cycle assay and apoptosis assay. The possibility of generating WJ-MSC from both distal ends of umbilical cord was about 37-50%. The adherent cells generated from FE and PE distal ends have exhibited similar morphological characteristics, presented as spindle-shaped fibroblast-like cells. As for immunophenotyping, comparable data were observed where MSC from both ends are positive for common MSC markers (CD29, CD73, CD90, CD106 and MHCclass I), negative expression for haematopoietic and immune markers (CD14, CD34,CD45, CD80, CD86 and MHC-class II). However, colony-forming unit assay of FEWJMSC showed more number of colonies and bigger in size as compared to the PEWJMSC. Moreover, FE-WJMSC showed rapid growth kinetics and shorter doubling time with an average of 34 hr. The predominant measurements in osteogenic and adipogenic induction assays via deposition of calcium and accumulation of lipid granules respectively demonstrated both MSC possessed an equivalent differentiation potency. Real time qPCR analysis on adipocytes and osteoblast differentiated from both ends showed up-regulation and down-regulation of specific set of genes, thus further confirmed the lineage specific differentiations. In term of immunomodulatory activity, MSC generated from both ends were able to suppress the proliferation of activated T cells in dose dependant manner and preserved cell viability simultaneously. Moreover, detention of T cells in G0/G1 phase of the cell cycle and arresting cells from entering into S phase were evident when FE-WJMSC were co-cultured with T cells. Furthermore, co-culture of FE-WJMSC with Jurkat cells has significantly increased the number of viable cells and rescued the cells from undergoing apoptosis. The current study displays the efficiency of generating MSC from different anatomical parts of human umbilical cord where FE-WJMSC can be regarded as a better source of MSC as compared to PE as they showed superior proliferation capacity, greater antiproliferative effect on immune cells and cell preservation ability from apoptosis. The higher expansion potential and enhanced functionality of FE-WJMSC at in vitro promise a quick and uninterrupted supply of MSC to encounter the clinical demand and research purposes.